Damage mechanics in engineering materials - Voyiadjis, George Z. (Studies in applied mechanics ;)
This book contains thirty peer-reviewed papers that are based on the presentations made at the symposium on "Damage Mechanics in Engineering Materials" on the occasion of the Joint ASME/ASCE/SES Mechanics Conference (McNU97), held in Evanston, Illinois, June 28-July 2, 1997. The key area of discussion was on the constitutive modeling of damage mechanics in engineering materials encompassing the following topics: macromechanics/micromechanical constitutive modeling, experimental procedures, numerical modeling, inelastic behavior, interfaces, damage, fracture, failure, computational